Évolution de la conscience morale hippocratique - Szałata, Kazimierz (Studia Ecologiae et Bioethicae, 2009)
This article is written in French. The article is a presentation of a lecture delivered on the International Science Session “Ethics, Finances and Responsibility”, which took place on October the 3rd and 4th, 2008 in Chateau de Bossey near Geneva. Searching for sources of ethic thoughts connected with difficult moral problems of the contemporary world, the author deals with the oldest, well known writing about the ethical practice of medicine, the Hippocratic Oath. Presenting the plenteous, philosophical- ethical contents of the Oath and the history of the growth on it the Hippocratic tradition enriched in experience of the Christian anthropology, the author identifies its norms and rules. Unfortunately, since the Enlightenment times, especially the nineteenth century Positivism the tradition has been seriously disturbed. Together with the questioning the Aristotelean-Thomism anthropology, the doubts appeared related to the matter of protection of life since the conception until the natural death. Whereas new, legal regulations connected with the progress of in medical studies request deep anthropological and philosophical reflection, which would bring back the importance of the forgotten Hippocratic tradition, where in the center of medical actions is a man who needs help.